The Effect Of Work Motivation On Employee Performance At Pt Bukit Indah Permai (BiIP) Malang City - Basory, Hartomy Akbar; Hellyani, Catharina Aprilia; Prasetyo, Neo Naufal (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Human resources quality can be measured through employee performance, which includes work results in terms of quality and quantity. To achieve high performance, companies need to pay attention to various influencing factors, work motivation as background research. The study purpose was to determine how work motivation affects employee performance in this company. The research object is PT Bukit Indah Permai (BIP) Malang City, a company in the housing midwife. The method used is quantitative method and SPSS. The study objective found that there was a positive and significant effect of work motivation variables on employee performance in the object of this research. This result is supported by the existence of a t count value of 4.472, which is higher than the t table value of 2.00856. In addition, this result is also supported by the findings of the ANOVA test which shows a p-value of 0.00 which is lower than the 0.05 level. The conclusion is that there is a positive and significant effect of work motivation variables on employee performance in this company.